We, Robots: Correlated Behaviour as Observed by Humans - Kroos, Christian; Herath, D. (Springer, 2014)
In this study participants judged on the relationship between two interacting robots, one of them a mobile robot, the other one a stationary, robot arm-based artistic installation with a high flexibility in orienting its anthropomorphic face. The robots’ behaviour was either (1) weakly correlated through a loose tracking function, (2) independently random, or (3) independently random, but constrained to the same closely limited area. It was found that the true degree of coupling was reflected on average in the rating responses but that pseudo-random behaviour of one of the robots was judged less random if a relationship between the two robots was present. We argue that such robot-robot interaction experiments hold great value for social robotics as the interaction parameters are under complete control of the researchers.